Thick Miocene eolian deposits on the Huajialing Mountains： The geomorphic evolution of the western Loess Plateau - Zhan, Tao; Guo, ZhengTang; Wu, HaiBin; Ge, JunYi; Zhou, Xin; Wu, ChunLin; Zeng, FangMing (Science China. Earth sciences, 2011)
The geomorphic evolution of northwestern China during the Cenozoic has been a subject of much geological interest because of its link with the uplift of the Himalayan-Tibetan complex. Much information about these changes is recoverable from the sedimentary sequences of the region. We report here on the thick eolian deposits mantling the Huajialing Mountains, a relatively flat mountain range in the western Loess Plateau. Correlation of magnetic susceptibility stratigraphy with the QA-I Miocene eolian sequence dates a 134.7 m section （NL-VII） for the interval from 18.7 to 11.8 Ma, as confirmed by micromammalian fossils. These eolian deposits demonstrate a much wider distribution of the Miocene eolian deposits, and also indicate that the topography contrasts in the western Loess Plateau, including the uplifts of the Huajialing Mountains and the bedrock highlands in the Qinan region, were formed by the early Miocene. The near-continuous Miocene eolian sequence from 18.7 to 11.8 Ma indicates that the substratum of Huajialing had not experienced any intense tectonic changes during this time interval, which suggests further, the relative tectonic stability of the nearby Tibetan Plateau.